Control and Monitoring System for Lighting on Dragon Fruit Plants - Kafriandeni, Okhari; Suhery, Cucu; Sari, Kartika; Malik, Abdul (Digital Innovation, 2025)
Dragon fruit plants require prolonged sunlight exposure to grow and develop optimally. One common practice among farmers is to provide artificial lighting at night. However, this lighting is still operated manually, which is considered less effective. To address this issue, this study developed a lighting control and monitoring system for dragon fruit plants. The system uses a NodeMCU ESP32 as the main controller, an LDR sensor for light detection, a relay module for lamp control, and Firebase with Flutter as the storage platform and real-time monitoring interface. The system is designed to automatically turn on the lamp when the light intensity detected by the LDR sensor falls below a predetermined threshold and to turn it off when the light is sufficient. Implementation of the system over two weeks produced a positive response to dragon fruit flowering, with blossoms appearing at several points on the plants. Accuracy testing of both the sensor readings and the automatic control system was conducted by comparing the number of correct data points with the total collected data. From a total of 5,131 data points recorded during testing, 4,745 matched the system’s logic, resulting in an accuracy of 92.47%. This result indicates that the system performs reliably in providing artificial lighting to extend the photosynthesis process in dragon fruit plants.